(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Diabetes mellitus remains a global health challenge and herbal medicines are known to be effective and safe for use in its management. Anthocleista nobilis is used in the traditional management of the disorder but this claimed use has not been validated. The present study was designed to establish and hence validate the use of the plant for the management of diabetes and also identify the bioactive phytoconstituents of the plant. The root and stem bark extracts of the plant were investigated for antidiabetic activity in alloxan-induced diabetic rats. The animals were treated orally with 100, 200 and 400 mg/kg bw of both extracts for seven days. The fasting blood glucose concentration (FBGC) of the animals was monitored for seven days with a glucometer. Ultra-high performance liquid chromatography/electrospray ionization-quadrupole time-of-flight mass spectrometric (UHPLC/ESI-QTOF-MS) technique was adopted for partial dereplication of secondary metabolites of the plant. The extracts significantly (p < 0.5) reduced the FBGC of the diabetic animals. Nine previously reported compounds in the genus Anthocleista were successfully dereplicated from the plant and identified to be scopoletin (1), anthocleistol (2), sweroside (3), djalonesone (4), fagaramide (5), lanosta-7, 24-dien-3-one (6), 1-hydroxy-3,7-dimethoxyxanthene (7), djalonensin (8) and secologanin (9). Numerous other prominent peaks were not identified and could be potential novel compounds. The traditional use of A. nobilis in the management of diabetes has been validated in the present study. The identified as well as the unidentified compounds could provide template for guided isolation of the antidiabetic and other bioactive constituents of the plant. Dhaka Univ. J. Pharm. Sci. 17(1): 19-28, 2018 (June)